DIGITAL PAYMENT: PROBABILITY IN MILLENIAL (CASE STUDY OF UINSU FEBI STUDENTS) - Muhammad Lathief Ilhamy Nasution (UNIVERSITAS PAKUAN, 2020)
The rapid technological advances with a very strong internet penetration make the Indonesian people connect to communicate instantly. This has indirectly changed the pattern of human life, especially in the activities of shopping, communicating and working and transacting money in order to spend their income. Therefore with the activities carried out the hope of access to financial services that are affordable, fast and easy to personally connect with various activities. Someone in the internet world makes demands that need to be addressed by modern financial service providers. Internet access has shown a significant increase. This is consistent with the publication of the Association of Internet Service Providers (APJII) in March 2015 stating an increase in internet users, namely from 71.9 million in 2013 to 88.1 million users at the end of 2014, or about 34.9% of the total population currently. This digital payment research shows that there is an increase in the quality of banking services in Indonesia. This is because the banking management has implemented it to reach all levels of Indonesian society, especially for millennials living in the FOR (frontier, outermost, and remote) areas.